2014
DOI: 10.9721/kjfst.2014.46.5.556
|View full text |Cite
|
Sign up to set email alerts
|

Potential Probiotic Lactobacillus plantarum P1201 to Produce Soy-yogurt with Enhanced Antioxidant Activity

Abstract: In this study, we evaluated changes in physicochemical properties, total phenol and isoflavone contents, and antioxidant activity during soymilk fermentation by a potential probiotic Lactobacillus plantarum P1201. The P1201 strain showed survival rates of 58.14% and 62.22% after 4 h exposure to acid and artificial gastric acid conditions (pH 2.5), respectively. The optimal conditions for soy-yogurt fermentation by L. plantarum were determined to be as follows: temperature of 35 o C, seed volume of 5.0%, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…It is important to note that the pH ranges found in the current study are consistent with the pH ranges found in the commercial yoghurt and with soy-yoghurt that was fermented with L. plantarum P1201 (Hwang et al, 2014). The L. plantarum P1201 used in this study exhibited different levels of β-glucosidase activity in 미생물학회지 제52권 제2호 SPMs during their growth under optimal conditions.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…It is important to note that the pH ranges found in the current study are consistent with the pH ranges found in the commercial yoghurt and with soy-yoghurt that was fermented with L. plantarum P1201 (Hwang et al, 2014). The L. plantarum P1201 used in this study exhibited different levels of β-glucosidase activity in 미생물학회지 제52권 제2호 SPMs during their growth under optimal conditions.…”
Section: Resultssupporting
confidence: 85%
“…A potential probiotic Lactobacillus plantarum P1201 that was previously isolated from a fermented beverage of plant extract was used as the starter organism for the fermentation (Hwang et al, 2014). Twelve authentic isoflavones were purchased as previously described by Lee et al (2013) Glacial acetic acid, Folin-Ciocalteu phenol reagent, 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) diammonium salt (ABTS), potassium persulfate, ferric chloride, sodium acetate, and 2,4,6-tripyridyl-s-triazine (TPTZ) were purchased from Sigma-Aldrich Chemical Co.…”
Section: Soybeans Microorganism Medium and Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations